Economic development and social change in South India. - Epstein, T.S. (Bombay, 1962)
Mrs. Epstein's emphasis is on the effect of economic oppor tunities on social institutions. In order to study the effect of social institutions on economic response, one would have to turn the method round, and study two villages where the economic opportunities were the same, and the social institutions were to begin with different. We know something about this problem, because we know how rapidly the market economy has spread around the globe, and how effectively it is forcing different social institutions everywhere to accommodate themselves to its require ments. Wherever we study the effect of economic change on institutions, the basic answer seems always to be the same, namely, that the love of money is a powerful institutional solvent.
Keywords: Socal Change .